Petrogenesis of Intrusive body in Northeast of Joveinan, North of Isfahan, Urumieh- Dokhtar magmatic zone - Shahzad Sherafat; Majid Zeidi; Mahnaz Khodami (Journal of Economic Geology)
Middle Miocene igneous rocks are located in the Northeast of Joveinan, the middle part of the Urumieh-Dokhtar Magmatic Belt. The igneous rocks have intruded into the Eocene volcano-sedimentary units. The rocks consist of diorite, quartzdiorite, and monzodiorite. They contain plagioclase, hornblende, biotite, pyroxene, orthoclase, quartz, and opaque minerals, and have granular to porphyroid textures. Field and petrographic evidence such as a lack of thermal metamorphism and graphic texture suggests that the rocks crystallized at a shallow depth. The rocks exhibit characteristics of I-type granitoids and a calc-alkaline nature with metaluminous affinities. The enrichment of large ion lithophile elements (LILEs) and the negative anomaly of Ta, Nb, and Ti elements in the primary mantle normalized diagram demonstrate subduction-related magmatism in the continental arc setting. The chondrite normalized pattern of the rocks (Lan/Ybn= 3.68-5.64) suggests a low degree of partial melting and the absence of garnet as a permanent phase in the source region. Based on the petrological data, the parental magma has been produced in the subduction setting of the collisional zone. The primary magma resulting from the partial melting of the subducted lithospheric mantle intruded into the continental crust. The magma underwent numerous changes and evolution during ascent and created the intrusive rocks of Northeast Joveinan.